Respuesta :
Answer:
[tex]-81t^{2}+16[/tex]
Step-by-step explanation:
we have
[tex](9t - 4)(-9t - 4)[/tex]
Applying distributive property
[tex](9t - 4)(-9t - 4)=(9t*-9t)+(9t*(-4))+(-4*(-9t))+(-4*(-4))\\=-81t^{2} -36t+36t+16\\=-81t^{2}+16[/tex]
Answer:
Option 2nd is correct
[tex]-81t^2+16[/tex]
Step-by-step explanation:
To find the product of:
[tex](9t-4)(-9t-4)[/tex]
We can write this as:
[tex]-(9t-4)(9t+4)[/tex]
Using identity rule:
[tex](a+b)(a-b) = a^2-b^2[/tex]
then;
[tex]-((9t)^2-(4)^2)[/tex]
⇒[tex]-(81t^2-16)[/tex]
Using distributive property i.e, [tex]a \cdot (b+c) = a\cdot b+ a\cdot c[/tex]
[tex]-81t^2+16[/tex]
Therefore, the following given product is, [tex]-81t^2+16[/tex]